Striking A Balance Between Job Creation and Sustainability: The Need to Establish A True Environmental Protection Authority in Indonesia - Dhiaulhaq AR, Muhammad Irfan; Heriyanto, Dodik Setiawan Nur (Faculty of Law, Jambi University, 2024)
The passing of Law No. 6 Year 2023 on Job Creation has seriously damaged relations between humans and the environment. This statute still provides a lot of convenience and freedom for industry to carry out economic activities and does not pay much attention to the environment. The imbalance between economic activities and environmental sustainability is indicated by the simplification of environmental permits carried out by the government. The government tends to simplify the permit by decreasing the degree of environmental protection obligation documents before establishing business in Indonesia. Using normative legal research methodology, this research examines the suitability of Job Creation Law to the basic principles of environmental sustainability. Apart from that, this research also examines the need to establish an Environmental Protection Authority in Indonesia to make sure that any activities within the territory of Indonesia comply with the environmental protection obligation. The results of this research show that the Job Creation Law prioritizes business interests to expand employment opportunities and ignores environmental conservation efforts. The simplification of permits in the Job Creation Law will accelerate environmental damage without control by diminishing the obligation to fulfill Environmental Impact Assessment (AMDAL) for business actors. If this situation gradually spirals out of control, this research proposes the establishment of an Environmental Protection Authority as a forum to ensure that every business activity in Indonesia must pay attention to environmental sustainability. Indonesia can learn from the practice of the developing country by empowering the Environmental Protection Authority to develop, supervise, and enforce environmental sustainability obligations.